2021
DOI: 10.1021/acsnano.1c00616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Barium Titanate Nanoparticles for Highly Efficient Hypoxic Tumor Therapy via Ultrasound Triggered Piezocatalysis and Water Splitting

Abstract: Hypoxia in a solid tumor microenvironment (TME) can lead to the overexpression of hypoxia-inducible factor-1α (HIF-1α), which correlates to tumor metastasis. Reactive oxygen species (ROS) induced tumor cell apoptosis is becoming a promising method in tumor treatment. Currently, the ROS generating systems, e.g., photodynamic treatment and sonodynamic treatment, highly depend on oxygen (O 2 ) in the tumor microenvironment (TME). However, the level of O 2 in TME is too low to produce enough ROS. Herein, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 48 publications
(95 reference statements)
2
113
0
Order By: Relevance
“…Moreover, tumor hypoxia not only causes insufficient therapeutic efficacy but also facilitates tumor angiogenesis, invasion, and metastasis. [ 13 ] To address this issue, enhancing the TME‐responsive supply of oxygen (O 2 ) to tumor sites has been considered as a feasible method for relieving tumor hypoxia. [ 13b ] Fortunately, overexpressed H 2 O 2 in the TME as an entrance can be decomposed into O 2 by catalase (CAT) or CAT‐like nanozyme, for improving the hypoxic TME and augmenting the •OH production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tumor hypoxia not only causes insufficient therapeutic efficacy but also facilitates tumor angiogenesis, invasion, and metastasis. [ 13 ] To address this issue, enhancing the TME‐responsive supply of oxygen (O 2 ) to tumor sites has been considered as a feasible method for relieving tumor hypoxia. [ 13b ] Fortunately, overexpressed H 2 O 2 in the TME as an entrance can be decomposed into O 2 by catalase (CAT) or CAT‐like nanozyme, for improving the hypoxic TME and augmenting the •OH production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] To address this issue, enhancing the TME‐responsive supply of oxygen (O 2 ) to tumor sites has been considered as a feasible method for relieving tumor hypoxia. [ 13b ] Fortunately, overexpressed H 2 O 2 in the TME as an entrance can be decomposed into O 2 by catalase (CAT) or CAT‐like nanozyme, for improving the hypoxic TME and augmenting the •OH production. It has been demonstrated that H 2 O 2 can be catalyzed into highly toxic •OH under acidic conditions, and into O 2 by nanozymes under neutral or weak alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…C 3 N 4 also serves as PDT agent to synergize with other therapeutic functionalities of the NPs. Similarly, other oxygen-generating photosensitizers have been used to construct NPs with US detectability [ 146 , 147 , 148 ]. For example, Gao et al constructed indocyanine green (ICG) modified hyaluronic acid nanoparticle encapsulating manganese dioxide (MnO 2 ) NPs, which are photosensitizers that react with endogenous H 2 O 2 to generate oxygen bubbles.…”
Section: Strategies Of Constructing Nanotheranosticsmentioning
confidence: 99%
“…The MPs and MPs@KGN dispersion were sonicated for 2 or 5 min using an ultrasound transducer (Chattanooga Co., Chattanooga, TN, USA, Thermal index/Ti = 0.9 and Mechanical index/Mi = 1.6) which had been applied in a previous study [39]. Meanwhile, they were soaked in PBS solution (pH = 7.4) at room temperature for one month.…”
Section: Surface Morphology and Size Distribution Measurements Of Plga Mpsmentioning
confidence: 99%